2016
DOI: 10.1111/apa.13581
|View full text |Cite
|
Sign up to set email alerts
|

Does noninvasive electrical stimulation of acupuncture points reduce heelstick pain in neonates?

Abstract: Aim Noninvasive electrical stimulation at acupuncture points (NESAP) for analgesia is used in children, but has not been widely studied in neonates. The purpose of this study was to determine if NESAP alone or in combination with sucrose relieved heelstick pain in neonates. Methods Term neonates (n=162) receiving routine heelsticks for newborn screening were enrolled following parental consent. All infants received facilitated tucking and nonnutritive sucking. Neonates were randomized to standard care, sucro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(78 citation statements)
references
References 33 publications
0
78
0
Order By: Relevance
“…MA has not previously been studied as an analgesic for neonatal procedural‐related pain. Previous studies have utilised different acupuncture modalities, including laser, acupressure and noninvasive electrical stimulation (NESAP) . Mitchell et al found that sucrose was the most important mitigating factor in reducing PIPP scores rather than NESAP in 162 full‐term newborn infants and that there were no differences in other markers of stress, such as heart rate variability or salivary cortisol levels .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MA has not previously been studied as an analgesic for neonatal procedural‐related pain. Previous studies have utilised different acupuncture modalities, including laser, acupressure and noninvasive electrical stimulation (NESAP) . Mitchell et al found that sucrose was the most important mitigating factor in reducing PIPP scores rather than NESAP in 162 full‐term newborn infants and that there were no differences in other markers of stress, such as heart rate variability or salivary cortisol levels .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have utilised different acupuncture modalities, including laser, acupressure and noninvasive electrical stimulation (NESAP) (18)(19)(20)(21). Mitchell et al found that sucrose was the most important mitigating factor in reducing PIPP scores rather than NESAP in 162 full-term newborn infants and that there were no differences in other markers of stress, such as heart rate variability or salivary cortisol levels (19). Studies that have shown no difference in pain secondary to acupuncture have used acupuncture modalities applied to local (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acupuncture activates pressure points leading to analgesia by increasing endogenous endorphins [32]. Body acupuncture and pain management is well known with the spinal pain pathways being recruited for attenuation of pain signaling in needle acupuncture.…”
Section: Acupuncturementioning
confidence: 99%
“…Anitha Mitchell et al randomised 162 term neonates undergoing routine heelsticks to receive usual care, namely facilitated tucking and a pacifier, or usual care with the addition of either NESAP or oral sucrose or NESAP plus sucrose. The premature infant pain profile scores were measured before, during and after the heelstick, and these indicated that NESAP was ineffective in reducing procedural pain, but sucrose seemed to be effective .…”
Section: Neonatal Acupuncture and Procedural Painmentioning
confidence: 99%